PARTICULARITIES OF MARKETING IN ROMANIAN SPORT - CRISTIAN ILIONI (Annals of the University of Petrosani: Economics)
Although sport has been around for centuries, the idea of a rational system of sports marketing is relatively new. The sports marketing specialist is required to market a product that is totally unpredictable, inconsistent and open to subjective interpretations. The expert in sports marketing must fulfill his role in an extremely competitive market, having a much smaller promotional budget than the organizations of the same size in other fields. The good part of this is represented by the media, willing to offer a broad presentation of the general product and the existence of many possibilities for generating income through association with the business or industry world.